2002
DOI: 10.21236/ada408816
|View full text |Cite
|
Sign up to set email alerts
|

Gender Not a Risk for Altitude Decompression Sickness Risk

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, □atherinq and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information including suggestions for reducing the burden to Department of Defense, Washington Headquarters Services Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 2 publications
1
32
0
Order By: Relevance
“…A similar conclusion was reached regarding risk of altitude decompression sickness. 13 Since the percentage of body fat, menstrual status, birth control drugs, or other allegedly risk-compounding factors were not examined in our patient population, we were unable to determine factors that might have predisposed women to DCS and consequently to a more vigorous recompression treatment. More studies are needed to clarify whether female gender is an independent risk factor for DCS.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion was reached regarding risk of altitude decompression sickness. 13 Since the percentage of body fat, menstrual status, birth control drugs, or other allegedly risk-compounding factors were not examined in our patient population, we were unable to determine factors that might have predisposed women to DCS and consequently to a more vigorous recompression treatment. More studies are needed to clarify whether female gender is an independent risk factor for DCS.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective trial of altitude exposure showed no net differences between men and women in risk for altitude decompression illness, but there was some association with menstrual cycle phase in subjects taking oral contraceptives 39. Prospective data on over 34 000 recreational dives by women submitting dive data to an ongoing project by the Diving Diseases Research Centre also suggests an association of risk with phase of the menstrual cycle, with problems more likely to be reported during the last and first weeks of the cycle 40 41.…”
Section: New Developments and Potential Translational Research Relevamentioning
confidence: 98%
“…For altitude exposure, DCS risk increased significantly with the weight/height ratio 89 and with weight. 126 The reports of Wise 122 and Curley and colleagues 125 stand out in finding no association between DCS and body fat. Wise 122 studied 1131 U.S. Navy divers, 63% of whom experienced DCS; Curley and associates 125 studied 376 U.S. Navy divers, 30% of whom experienced DCS.…”
Section: Individual Factorsmentioning
confidence: 99%